2011
DOI: 10.1108/09675421111130621
|View full text |Cite
|
Sign up to set email alerts
|

Organizational culture and performance: the role of management accounting system

Abstract: Purpose -This study aims to examine the combined effect of the interactive and diagnostic management accounting system (MAS) use and organizational culture on performance. Using the contingency perspective, this study suggests that the performance is enhanced by the interaction of organizational culture and the simultaneous use of both types of MAS. Design/methodology/approach -Data were collected through a questionnaire, and responses from 147 senior managers provide support for the research model and demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 48 publications
3
24
0
3
Order By: Relevance
“…Although the hypothesis was motivated by the literature suggesting that the use of the diagnostic system is less frequent (Agbejule, 2011), most of the authors indicated it as a restriction (Davila, 2005;Simons, 1995). Arjaliès and Péan (2009) and Malagueño and Bisbe (2010) obtained similar results.…”
Section: Hypothesis 1 External Stimuli Have a Positive Association Wmentioning
confidence: 99%
“…Although the hypothesis was motivated by the literature suggesting that the use of the diagnostic system is less frequent (Agbejule, 2011), most of the authors indicated it as a restriction (Davila, 2005;Simons, 1995). Arjaliès and Péan (2009) and Malagueño and Bisbe (2010) obtained similar results.…”
Section: Hypothesis 1 External Stimuli Have a Positive Association Wmentioning
confidence: 99%
“…Improving firm performance is something that most organizations strive to achieve [119]. Some of the factors reported in literature to have an influence on organizational performance and its improvement include: organizational culture [120], organization's environment and strategy [121], individual and organizational learning [122], and employee involvement and commitment to organizational goals [123]. Literature provides many definitions for organizational performance.…”
Section: Organizational Performance (Op)mentioning
confidence: 99%
“…Code of ethics communicated by the corporate should be able to train employees to behave according to corporate goals not only used as manuals. This has an impact on reducing financial, legal and reputation risks and improving organizational performance [24].…”
Section: Aptikom J Csitmentioning
confidence: 99%